Import tariffs and informal labour market: A Computable General Equilibrium (CGE) analysis for Turkey - Hale Akbulut; Hüseyin Taylan Eğen (Review of Economic Analysis (REA), 2021)
From the 1980s to onwards trade liberalization policies have been widely used in many countries. This process has significant impacts on many economic aspects one of which is on the labour market. However, the direction of the relationship between trade reforms and the labour market is controversial. This study aims to analyse the effects of a specific trade reform of import tariff changes on the formal and informal labour market for Turkey. For that purpose, we benefit from Computable General Equilibrium (CGE) Model that relies on nonlinear simultaneous equations. We construct an updated Social Accounting Matrix (SAM) which is compatible with our model. Our findings indicate that while there is a positive relationship between formal labour employment in total and import tariff rates, the negative relationship occurs between informal employment and tariff rates.
Keywords: C68; H20; H21; H30; F16; 330; Informal Labour; Import Tariffs; CGE; Turkey